2020
DOI: 10.1016/j.tru.2020.100017
|View full text |Cite
|
Sign up to set email alerts
|

Thrombosis of pulmonary vasculature despite anticoagulation and thrombolysis: The findings from seven autopsies

Abstract: Background Venous thromboembolism (VTE) with the prevalence of pulmonary microcirculatory thrombosis is considered a common complication of novel coronavirus disease (COVID-19) that develops despite anticoagulation. Methods The clinical course of the disease and the autopsy findings of seven deceased patients with verified COVID-19 were analyzed. The chest computed tomography (CT) scan was routinely performed while CT pulmonary angiography and a duplex ultrasound scan (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
7
0
6

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 26 publications
(45 reference statements)
1
7
0
6
Order By: Relevance
“…Others like dementia [ 23 ], Immunosuppressive medication [ 24 ], Liver steatosis, and cerebral small vessel disease [ 31 ]. Gastric carcinoma, hepatocellular carcinoma, basal cell carcinoma [ 34 ] Graft-versus-host disease following cancer [ 44 ] Bone marrow transplantation (BMT) [ 44 ], and HIV positive status [ 45 ] Lungs Gross changes observed Thrombosis and embolic phenomenon in small- and large- sized arteries [ 4 6 , 9 , 14 , 17 , 18 , 24 , 36 , 40 , 42 , 43 , 45 , 46 , 48 , 51 , 52 , 59 , 60 , 66 , 68 , 70 , 76 , 80 , 83 , 86 , 88 , 92 94 , 97 , 104 , 105 ] Pulmonary infarction, haemorrhagic infarcts [ 6 , 27 , 78 , 80 , 83 ]. Fibrosis [ 5 , 21 , 22 ].…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations
“…Others like dementia [ 23 ], Immunosuppressive medication [ 24 ], Liver steatosis, and cerebral small vessel disease [ 31 ]. Gastric carcinoma, hepatocellular carcinoma, basal cell carcinoma [ 34 ] Graft-versus-host disease following cancer [ 44 ] Bone marrow transplantation (BMT) [ 44 ], and HIV positive status [ 45 ] Lungs Gross changes observed Thrombosis and embolic phenomenon in small- and large- sized arteries [ 4 6 , 9 , 14 , 17 , 18 , 24 , 36 , 40 , 42 , 43 , 45 , 46 , 48 , 51 , 52 , 59 , 60 , 66 , 68 , 70 , 76 , 80 , 83 , 86 , 88 , 92 94 , 97 , 104 , 105 ] Pulmonary infarction, haemorrhagic infarcts [ 6 , 27 , 78 , 80 , 83 ]. Fibrosis [ 5 , 21 , 22 ].…”
Section: Introductionmentioning
confidence: 99%
“…Fibrosis [ 5 , 21 , 22 ]. ARDS [ 47 , 62 ] Microscopic/histopathological changes noted Diffuse aveolar damage – DAD [ 4 , 6 , 9 , 14 , 17 , 20 25 , 30 , 31 , 35 , 36 , 40 , 41 , 43 , 46 , 49 , 50 , 52 , 55 58 , 64 , 65 , 68 , 69 , 71 , 74 , 77 , 78 , 80 , 81 , 83 , 86 88 , 92 94 , 97 , 104 106 ] Exudative DAD seen within 8 days period. Advanced DAD seen after 17 days.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…An elegant pathophysiological scheme for COVID-19-related cardiac injury has only recently been put forward (13) and outlines numerous co-existing factors: indirect myocardial injury via a cytokine storm; organ failure due to systemic inflammatory response syndrome (SIRS); oxygen supply and demand mismatch due to acute respiratory failure; cardiotoxicity from treatments; coronary thrombosis due to plaque rupture caused by shear stress; arrhythmia; and embolic complications due to SIRS. Post-mortem studies have demonstrated microthrombi within the pulmonary vasculature (14). In addition, direct myocardial injury may be caused by inflammation following direct viral entry via ACE-2 receptor binding and cellular entry.…”
Section: Introductionmentioning
confidence: 99%